Differential expression of neurexin genes in the mouse brain. Issue 12 (25th February 2019) - Uchigashima, Motokazu; Cheung, Amy; Suh, Julie; Watanabe, Masahiko; Futai, Kensuke
Abstract: Synapses, highly specialized membrane junctions between neurons, connect presynaptic neurotransmitter release sites and postsynaptic ligand‐gated channels. Neurexins (Nrxns), a family of presynaptic adhesion molecules, have been characterized as major regulators of synapse development and function. Via their extracellular domains, Nrxns bind to different postsynaptic proteins, generating highly diverse functional readouts through their postsynaptic binding partners. Not surprisingly given these versatile protein interactions, mutations and deletions of Nrxn genes have been identified in patients with autism spectrum disorders, intellectual disabilities, and schizophrenia. Therefore, elucidating the expression profiles of Nrxns in the brain is of high significance. Here, using chromogenic and fluorescent in situ hybridization, we characterize the expression patterns of Nrxn isoforms throughout the brain. We found that each Nrxn isoform displays a unique expression profile in a region‐, cell type‐, and sensory system‐specific manner. Interestingly, we also found that αNrxn1 and αNrxn2 mRNAs are expressed in non‐neuronal cells, including astrocytes and oligodendrocytes. Lastly, we found diverse expression patterns of genes that encode Nrxn binding proteins, such as Neuroligins ( Nlgns ), Leucine‐rich repeat transmembrane neuronal protein ( Lrrtms ) and Latrophilins ( Adgrls ), suggesting that Nrxn proteins can mediate numerous combinations of trans‐synaptic interactions. Together, our anatomical profiling of Nrxn gene expression reflects the diverse roles of Nrxn molecules. Abstract : Here, we used chromogenic and fluorescence in situ hybridization to characterize the expression pattern of neurexin (Nrxn) isoforms. While each Nrxn isoform displayed a unique expression profile in different regions and cell types, αNrxn1 and αNrxn2 mRNAs were interestingly expressed in non‐neuronal cells, including astrocytes and oligodendrocytes. Nrxn postsynaptic binding partners, such as Neuroligins and Latrophilins were also diversely expressed throughout the mouse brain, emphasizing the numerous combinations of trans‐synaptic interactions that can occur between these molecules.